Determinación de valores séricos y factores asociados en caninos domésticos (canis familiaris) en el Barrio Mulaló Centro. - Quevedo Bravo, Sara Gabriela (2019)
The following investigation was made at Mulaló Centro neighborhood, San Fernando de Mulaló Parish, on Latacunga canton, studying 75 domestic canines (Canis familiaris) selected randomly and grouped by age, where most of them are 1 to 5 years old, attending the matter that there is not a proper diagnosis for the context of the population. Blood samples were taken for blood count and blood chemistry, each sample was archived along with a clinical tab nof the animal and a poll to the owner about the environment and the usual practices that the animal has, in order to determine the associated factors and value serum of canines at mentioned area. With the poll it was found that 85% of the canines have plenty of space, 49% have a dog house to cover themselves from the sun or rain, 54% is fed with house-made food, 89% have water, 70% have been vaccinated, 37% of animals have not been dewormed and 45% are taken to the vet only when they are sick. In the blood count it was seen that 6,6% canines have elevated erythrocytes and 6,6% have diminished erythrocytes; 1,3% show elevated platelets and 34% show diminished platelets; 8% show leukocytosis and 9,3% show leucopenia. In blood chemistry 20,7% of canines show elevated glucose and 8% diminished glucose; 30,7% have augmented urea, 33,3% show elevated creatinine and 2,7% show diminished creatinine; 24% have elevated AST; 21,3% elevated ALT; 4% of canines show elevated total proteins and 26,7%, diminished proteins, concluding that results were similar to referential data from investigations in different populations, nevertheless, it was found that several values differ from the average range, revealing an alteration in the organism of individuals, which is verified by the result of the polls, where most of the canines show bad nutrition, lack deworming, vaccines and vet control.